Kajian Pendapat Ulama’: Analisis Hadis terhadap Pendapat Turunnya Wahyu Berbahasa Arab serta Kedudukan Kalamulloh dan Ilham bagi Selain Nabi - Hifdhul Ulum; Moh Mahfudz Ali Amari Sya’roni; Nur Hannan (Al-Qadim: Jurnal Tafsir dan Ilmu Tafsir, 2026)
This study aims to analyze the nature of the revelatory language in the Quran, the status of hadiths concerning the revelation in Arabic, the concept of Kalamullah (the Word of God), and the epistemological status of inspiration (ilham) and dreams (ru'yah) for non-prophets. Employing a qualitative research methodology with a library research approach, this study examines various classical and contemporary literatures to map the theological and ushul shariah (principles of Islamic law) perspectives of scholars. The findings indicate an academic debate between scholars who view Arabic as the original language of revelation and those who emphasize linguistic adaptation to the community of the receiving prophet. Within theological discourse, the debate surrounding Kalamullah gives rise to differing concepts among the Mu'tazilite, Jahmite, and Ash'arite schools regarding the nature of God's speech. Furthermore, this study underscores a strict boundary in Islamic epistemology: ilham, kashf (spiritual unveiling), and dreams (ru'yah) for non-prophets are strictly personal and subjective. Consequently, these spiritual experiences do not satisfy the criteria for scientific verification and cannot serve as authoritative proofs (hujjah) in determining sharia rulings or interpreting the Quran. This restriction is crucial to safeguarding the authenticity of sharia from ambiguities in contemporary religious practices. Regarding the text, not all hadiths explaining that the Quran was revealed in Arabic are authentic (sahih), such as the narration by Al-Hakim. Conversely, the hadiths narrated by Al-Bukhari exhibit an authentic (sahih).